Protease resistance of porcine acidic mammalian chitinase under gastrointestinal conditions implies that chitin-containing organisms can be sustainable dietary resources. Issue 1 (December 2017) - Tabata, Eri; Kashimura, Akinori; Wakita, Satoshi; Ohno, Misa; Sakaguchi, Masayoshi; Sugahara, Yasusato; Imamura, Yasutada; Seki, Shiro; Ueda, Hitoshi; Matoska, Vaclav; Bauer, Peter; Oyama, Fumitaka
Abstract Chitin, a polymer ofN -acetyl-D-glucosamine (GlcNAc), is a major structural component in chitin-containing organism including crustaceans, insects and fungi. Mammals express two chitinases, chitotriosidase (Chit1) and acidic mammalian chitinase (AMCase). Here, we report that pig AMCase is stable in the presence of other digestive proteases and functions as chitinolytic enzyme under the gastrointestinal conditions. Quantification of chitinases expression in pig tissues using quantitative real-time PCR showed that Chit1 mRNA was highly expressed in eyes, whereas the AMCase mRNA was predominantly expressed in stomach at even higher levels than the housekeeping genes. AMCase purified from pig stomach has highest activity at pH of around 2–4 and remains active at up to pH 7.0. It was resistant to robust proteolytic activities of pepsin at pH 2.0 and trypsin and chymotrypsin at pH 7.6. AMCase degraded polymeric chitin substrates including mealworm shells to GlcNAc dimers. Furthermore, we visualized chitin digestion of fly wings by endogenous AMCase and pepsin in stomach extract. Thus, pig AMCase can function as a protease resistant chitin digestive enzyme at broad pH range present in stomach as well as in the intestine. These results indicate that chitin-containing organisms may be a sustainable feed ingredient in pig diet.